A reciprocal – reflective approach to learning: concept and model - Lyons, Paul; Bandura, Randall (European journal of training and development, 2025)
Purpose The purpose of this paper aimed primarily at the practitioner is to offer foundational information regarding reciprocal-reflective approach to learning (RRAL). Presentation and explanation include conceptual and theory grounding of the processes to be initiated by a manager for collaboration with an employee. A detailed model reflective of the approach is presented. Conceptual and practice-aimed information may be adapted for training and development. Design/methodology/approach Explanations of employee learning often place the manager in role(s) of teacher, guide, coach and/or expert. Proposed here is an approach in which manager and individual employee, jointly, make use of a learning approach which is representative of an experiential, action or problem-based form of learning from which they both can learn. The manager can initiate the process in which both participants collaborate to identify some specific, shared learning goals aimed at the matters under consideration. Other goals, likely more personal in the case of each participant, may also be identified and efforts made to help one another attain progress regarding such goals. The RRAL process as explained mirrors a bifurcation of instrumental behaviors (focus on learning activities) and emotional behaviors (caring and sharing resulting in a strengthened relationship and trust). Findings Relying on research that clearly identifies various supportive behaviors on the part of the manager, a detailed example of a plan is provided. The plan is driven by shared aims, focus, feedback and adjustment. In addition to individual learning goals, the manager has the opportunity to make her/his own role adjustments that lead to positive, supportive actions stimulating the quality of the relationship with the employee including the building of trust. Practical implications Using the example provided as a guide can be very helpful to a manager with limited experience in instigating employee learning and change. Initial use may be regarded as an experiment subject to much analysis and discussion by both participants as they contemplate how to work together in future reciprocal learning endeavors. Originality/value Currently, there is little research available that expresses how manager and employee can work as partners on some matter (change, problem, improvement) in a collaborative, reciprocal fashion. This paper, as an example, should demonstrate that skills and knowledge of both participants can improve and progress made regarding the issue at hand. The RRAL can be fashioned by the participants to yield progress and a more positive relationship.